If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = v + -8 Reorder the terms: -2 = -8 + v Solving -2 = -8 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. -2 + -1v = -8 + v + -1v Combine like terms: v + -1v = 0 -2 + -1v = -8 + 0 -2 + -1v = -8 Add '2' to each side of the equation. -2 + 2 + -1v = -8 + 2 Combine like terms: -2 + 2 = 0 0 + -1v = -8 + 2 -1v = -8 + 2 Combine like terms: -8 + 2 = -6 -1v = -6 Divide each side by '-1'. v = 6 Simplifying v = 6
| -12+x=-17 | | 7x+14y=122 | | -9=r-16 | | 6p^2-13p+7=0 | | -x^2-40x-76=0 | | 26=x+17 | | -2-5(1-4)=127 | | 14=-4+n | | 3(2+v)= | | 18=6-3-3 | | -4x-6=12y | | 4(x)+2(23-x)=62 | | k-20=-40 | | 4x-6=12y | | 9.8x+2.4y-8.1=0 | | -20+a=-2 | | -25=-16+N | | 4sin(0)= | | f(x)=2x^2-12x-27 | | 3k^2+16k+16=0 | | g(f(x))=h(g(x)) | | 11x+3=-25 | | -6w-2(-2x+5w)+5x= | | -4(v-1)=5v-32 | | 20k+20=-20+18k | | 5x-4=5(x-2) | | h^2-8h-9=0 | | 2X-4=4y | | -7u-35=7(u-7) | | 2.7x+6.1+3.2-4.9= | | 2[x+4]=-5x+1 | | 7w-1=14+1+7w |